Tuning the solid-state emission of liquid crystalline nitro-cyanostilbene by halogen bonding - Nath, Subrata; Kappelt, Alexander; Spengler, Matthias; Roy, Bibhisan; Voskuhl, Jens; Giese, Michael (Beilstein Journal of Organic Chemistry, 2021)
The first example of halogen-bonded fluorescent liquid crystals based on the interaction of iodofluorobenzene derivatives with nitro-cyanostilbenes is reported. The systematic variation of the fluorination degree and pattern indicates the relevance of the halogen bond strength for the induction of liquid crystalline properties. The modular self-assembly approach enables the efficient tuning of the fluorescence behaviour and mesomorphic properties of the assemblies.
Keywords: fluorescence; halogen bonding; liquid crystal

(untitled) - Yan, X.; Wang, F.; Zheng, B.; Huang, F. (Chem. Soc. Rev., 2012)

(untitled) - Yang, Y.; Urban, M. W. (Chem. Soc. Rev., 2013)

(untitled) - Metrangolo, P.; Meyer, F.; Pilati, T.; Resnati, G.; Terraneo, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kato, T.; Mizoshita, N.; Kishimoto, K. (Angew. Chem., Int. Ed., 2006)

(untitled) - Nguyen, H. L.; Horton, P. N.; Hursthouse, M. B.; Legon, A. C.; Bruce, D. W. (J. Am. Chem. Soc., 2004)

(untitled) - Paleos, C. M.; Tsiourvas, D. (Liq. Cryst., 2001)

(untitled) - Pfletscher, M.; Mezger, M.; Giese, M. (Soft Matter, 2018)

(untitled) - Saccone, M.; Catalano, L. (J. Phys. Chem. B, 2019)

(untitled) - Chen, Y.; Yu, H.; Zhang, L.; Yang, H.; Lu, Y. (Chem. Commun., 2014)

(untitled) - Fernandez-Palacio, F.; Poutanen, M.; Saccone, M.; Siiskonen, A.; Terraneo, G.; Resnati, G.; Ikkala, O.; Metrangolo, P.; Priimagi, A. (Chem. Mater., 2016)

(untitled) - Bisoyi, H. K.; Li, Q. (Angew. Chem., Int. Ed., 2016)

(untitled) - Saccone, M.; Spengler, M.; Pfletscher, M.; Kuntze, K.; Virkki, M.; Wölper, C.; Gehrke, R.; Jansen, G.; Metrangolo, P.; Priimagi, A.; Giese, M. (Chem. Mater., 2019)

(untitled) - Tothadi, S.; Sanphui, P.; Desiraju, G. R. (Cryst. Growth Des., 2014)

(untitled) - Desiraju, G. R. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Tothadi, S.; Desiraju, G. R. (Chem. Commun., 2013)

(untitled) - Allen, F. H.; Goud, B. S.; Hoy, V. J.; Howard, J. A. K.; Desiraju, G. R. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Allen, F. H.; Lommerse, J. P. M.; Hoy, V. J.; Howard, J. A. K.; Desiraju, G. R. (Acta Crystallogr., Sect. B: Struct. Sci., 1997)

(untitled) - Palakollu, V.; Kanvah, S. (New J. Chem., 2014)

(untitled) - Bruce, D. W.; Metrangolo, P.; Meyer, F.; Pilati, T.; Präsang, C.; Resnati, G.; Terraneo, G.; Wainwright, S. G.; Whitwood, A. C. (Chem. – Eur. J., 2010)

(untitled) - Tschierske, C. (Chem. Soc. Rev., 2007)

(untitled) - Saccone, M.; Blanke, M.; Daniliuc, C. G.; Rekola, H.; Stelzer, J.; Priimagi, A.; Voskuhl, J.; Giese, M. (ACS Mater. Lett., 2019)

(untitled) - An, B.-K.; Kwon, S.-K.; Jung, S.-D.; Park, S. Y. (J. Am. Chem. Soc., 2002)

(untitled) - Zhu, L.; Zhao, Y. (J. Mater. Chem. C, 2013)

(untitled) - Gupta, R. K.; Pathak, S. K.; De, J.; Pal, S. K.; Achalkumar, A. S. (J. Mater. Chem. C, 2018)

(untitled) - Mei, J.; Leung, N. L. C.; Kwok, R. T. K.; Lam, J. W. Y.; Tang, B. Z. (Chem. Rev., 2015)